Fall of ruin and wrath [large type] - Armentrout, Jennifer L. (Armentrout, Jennifer L. Awakening, 2023)
"Long ago, the world was destroyed by gods. Only nine cities were spared. Separated by vast wilderness teeming with monsters and unimaginable dangers, each city is now ruled by a guardian. Born with an intuition that never fails, Calista knows her talents are of great value, so she lives hidden as a courtesan of the Baron of Archwood. When her intuition leads her to a prince, the voice inside her blazes with warning--and promise. When the prince takes an interest in Calista, she becomes his companion. But with knights and monsters at her city gates and a hungry prince in her bed, Calista must choose: follow her intuition to safety or follow her heart to her downfall"--